THE CONTRIBUTIONS OF ASSISTIVE TECHNOLOGY FROM THE PERSPECTIVE OF INCLUSIVE EDUCATION OF CHILDREN WITH AUTISM SPECTRUM DISORDER - ASD - Maia Cardoso, Elizabeth (Revista Gênero e Interdisciplinaridade, 2023)
This article brings a bibliographic review on the contributions of Assistive Technology in the perspective of inclusive education for children with Autism Spectrum Disorder - ASD. The general objective is to investigate how the use of Assistive Technology can favor the teaching and learning of students with Autism Spectrum Disorder (ASD). The investigation of the subject takes place through a bibliographical review, with a descriptive purpose, with data processing through a qualitative approach. The bibliographic procedure allows one to become aware of relevant material, based on what has already been published in relation to the subject, so that a new approach can be outlined on the same, reaching conclusions that can serve as a basis for the research. Any published information (printed or electronic) is likely to become a source of consultation. The conclusion points out that Assistive Technology can provide people with Autism Spectrum Disorder with the means to access and participate in educational, social and recreational opportunities, strengthening physical and mental function and improving self-esteem, in addition to reducing the costs of educational services and of individual support. By improving access to education and increasing school performance, Assistive Technology (AT) can have a positive socioeconomic effect on the lives of children with disabilities.